Being and experiencing soccer in Juárez-Mexico - Lara-Rodríguez, Luis Manuel (Universidad Centro Latinoamericano de Economía Humana (Universidad CLAEH), 2021)
Ciudad Juárez-Mexico, like many other cities, concentrates its identity constitution processes in scenarios and spaces of disagreement between what is experienced, what is thought, and daily expectations. Bordering northern Mexico, the city has endured periods of public insecurity and violence in recent decades, such as femicides and the "war" against organized crime. However, at the same time, during the final two decades of the twentieth century to date, a socio-cultural manifestation emerged concerning professional football (soccer): the citizens identification with the highest national circuit’s teams. Juárez has been historically characterized as a region fond of baseball, basketball and athletics, with a certain rejection of soccer, especially due to its distance from the center and south of the country, where soccer is more firmly stablished. The article aims to describe some socio-cultural prints, as representations of soccer and the city. They are inscribed in an identity conformation of violence, but also of hope and exaltation, involving processes that articulate migration, duality, the centralism-regionalism dyad, national and international influences and meanings.